Monetary transmission in diverse economies - Mahadeva, Lavan; Sinclair, P. J. N. (Cambridge University Press, 2002)
This volume explains different aspects of the transmission mechanism. It scrutinises the relevance of practical issues such as asymmetries, recent structural changes and estimation errors using data on the US, Euro area and developing countries. Also focuses on modelling crucial aspects including productivity, the exchange rate and the monetary sector.